Time-resolved spectroscopy of CsI(CO3) scintillator; Journal of Luminescence; Vol. 173 - Yakovlev V. Yu. Viktor Yurjevich; Trefilova L. N. Larisa Nikolaevna; Lebedinsky A. M. Aleksey Mikhaylovich; Zeyin D. Daulet; Dubtsov I. N. Igor Nikolaevich (2016, 2016)
Title screen